Management of Acute Uncomplicated Stanford B Aortic Dissection in The Era of Endovascular Repair: A Case Report - Putri Annisa Kamila; Novi Kurnianingsih; Sasmojo Widito; Djanggan Sargowo; Budi Satrijo (Universitas Brawijaya, 2020)
Introduction:Uncomplicated type B aortic dissections have been traditionally treated with medication therapy. While it may provide good short-term results, longterm prognosis may be less favorable. With improvements in endovascular repair and the potential risk of disease progression, thoracic endovascular aortic repair (TEVAR) has been considered inpatients with uncomplicated type B aortic dissection. We present the case of 78-year-old gentleman who presented with acute uncomplicated type B aortic dissection managed by endovascular repair Case illustration:A 78 year-old hypertensive patient admitted to the hospital with persistent chest discomfort and cough for 2 weeks. The CT aortic angiogram showed type B dissection. Based on the recent guidelines, TEVAR should be considered in patients with uncomplicated type B aortic dissection, thus we prepared the patient for TEVAR procedure. First we established multidisciplinary vascular team for the pre-procedural preparation of the patient. We perform careful measurement through detailed CT angiography reconstruction from carotid to femoral arteries. We found proximal diameter was 30-35mm, distal diameter was 23mm and landing zone right after left brachial ostium, suitable for stent graft Valiant Captivia 36-32x150mm. The CT also showed that both femoral artery were normal, we decided to use right femoral artery as the access. We proceed to the procedure 2 days later, under general anaesthesia, digital subtraction angiography revealed dissection of descending aorta, and selected device was inserted. Subsequent contrast injection revealed total occlusion of the false lumen. Patient was transferred to ICU for postprocedural care, and extubated the day after. The hospital stay was uneventful, and one-month follow up CT shows no endoleak. Conclusion :Management of uncomplicated Stanford B dissections is very challenging. TEVAR has emerged as an alternative to surgery with lower morbidity and mortality rates that might offer good long-term results.